INCREASING THE POWER OF PUBLIC SPEAKING (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
The advancement in technology revolutionized our lives significantly in recent years. To achieve any success, it is not enough to be knowledgeable person, sometimes we faced some situation which we must speak in front of audience. But this is becoming an actual issue nowadays, because the great number of individuals are unable to overcome their fear and excitement and cannot speak freely in front of the public and they always blame themselves. Such kind of circumstances require a big skill and everyone should know how to kill the panic.